Liberating Luther : A Lutheran Theology from Latin America - Westhelle, Vítor, 1952-2018 (Book collections on Project MUSE., 2021)
Until his untimely death, Vitor Westhelle's incisive scholarship shaped a generation. As a continuation of that legacy, presented here for the first time in English is a collection of Westhelle's Portuguese-language essays. In this collection, he addresses the most important issues of our day, including the cross and death, the ecological crisis, the ecumenical movement, the church's misuse of power, Luther's law-gospel dialectic, and the role of European theology in the conquest of the Americas.